Transfusion of cadaveric blood: an outstanding achievement of Russian transplantation, and transfusion medicine (to the 85th anniversary since the method establishment) - M. Sh. Khubutiya; S. A. Kabanova; P. M. Bogopol'skiy; S. P. Glyantsev; V. A. Gulyaev (Трансплантология (Москва), 2016)
The article reveals some little known facts of emergence the idea, development of the problem, and features of introduction of cadaveric blood transfusion method into clinical practice and the history of its development since the 20-ies of twentieth century to the present.